Intrinsic disorder in proteins: Relevance to protein assemblies, drug design and host-pathogen interactions - Blundell, Tom L.; Gupta, Munishwar N.; Hasnain, Seyed E. (Progress in biophysics and molecular biology, 2020)
Intrinsic disorder in proteins resulting in considerable variation in structure can lead to multiple functions including multi-specificity and diverse pathologies. Protein interfaces can involve disordered regions that assemble through a concerted-fold-and-bind mechanism. The binding involves both enthalpic and entropic gains by exploiting ‘hot spots’ on the partner and displacing water molecules placed in thermodynamically unfavorable situations. The examples of Rad51-BRCA2 and Artemis-DNA-PKCs/LigIV complexes illustrate this in the context of drug design. This overview tracks the seamless involvement of protein disorder in multi-specificity of biocatalysts, protein assembly formations and host-pathogen interactions, where intrinsic disorder can in Mycobacteria, compensate for genome reduction by carrying out multiple functions and in some RNA viruses facilitate adaption to the host. These present challenging opportunities for designing new drugs and interventions.